Crosstalk Between the Oxidative Stress and Glia Cells After Stroke: From Mechanism to Therapies - Zhu, Ganggui; Wang, Xiaoyu; Chen, Luxi; Lenahan, Cameron; Fu, Zaixiang; Fang, Yuanjian; Yu, Wenhua (Frontiers in Immunology, 2022)
Stroke is the second leading cause of global death and is characterized by high rates of mortality and disability. Oxidative stress is accompanied by other pathological processes that together lead to secondary brain damage in stroke. As the major component of the brain, glial cells play an important role in normal brain development and pathological injury processes. Multiple connections exist in the pathophysiological changes of reactive oxygen species (ROS) metabolism and glia cell activation. Astrocytes and microglia are rapidly activated after stroke, generating large amounts of free radicals (ROS) via mitochondrial and NADPH oxidase pathways, causing oxidative damage to the glial cells themselves and neurons. Meanwhile, ROS cause alterations in glial cell morphology and function, and mediate their role in pathological processes, such as neuroinflammation, excitotoxicity, and blood-brain barrier damage. In contrast, glial cells protect the Central Nervous System (CNS) from oxidative damage by synthesizing antioxidants and regulating the Nrf2 pathway, among others. Although numerous previous studies have focused on the immune function of glial cells, little attention has been paid to the role of glial cells in oxidative stress. In this paper, we discuss the adverse consequences of ROS production and oxidative-antioxidant imbalance after stroke. In addition, we further describe the biological role of glial cells in oxidative stress after stroke, and we describe potential therapeutic tools based on glia cells.